Regulatory B Cells in Seropositive Myasthenia Gravis versus Healthy Controls - Karim, Md Rezaul; Zhang, Hong-Yan; Yuan, Jiang; Sun, Qiang; Wang, Yun-Fu (Frontiers in Neurology, 2017)
Objective: to find out if the failure in immunotolerance of Myasthenia Gravis (MG) is a possible aspect of deduction in Breg cells and to characterize B cell subsets in MG. Methods: flow cytometry detection and ELISA assays in peripheral blood films of 10 MG patients and 10 healthy controls (HCs) were performed after isolation of B cells. The CD19+CD5+CD1d+ Breg cells percentages were measured to complement a B cell phenotype assay and frequencies of B cell subsets. The clinical outcome measures and immunological variables of patients with MG were compared with HCs. Results: patients with MG had relatively lowered percentages of CD19+CD5+CD1d+ Breg cells as compared to HCs. The production of Interleukin (IL) -10 and Transforming Growth Factor (TGF) -β1 was relatively lesser in patients with MG than HCs which were linked with more severe of MG disease status according to Myasthenia Gravis Foundation of America (MGFA) clinical classification. The reduction of cytokine production was more significant for IL-10 than TGF-β1 when compared to HCs. Conclusion: it has been observed that the reduced number of B cells are able to produce IL-10 in MG patients but lesser than compared to HCs. The Bregs reduction mainly was regarded by the severity of disease status which was highly significant and also by disease duration which was statistically significant as well. The findings of the measurement of B cell phenotype assay and frequencies of B cell subsets between MGs and HCs give us new ideas to develop B-cell mediated therapies of MG such as ① isolated B cells of MGs could be cultured with steroids eg. dexamethasone in vitro to see if it induces the CD19+CD5+CD1d+ Breg cells. ② it may observe whether induced CD19+CD5+CD1d+ Bregs have higher production of IL-10 and TGF-β1, as both are linked with disease severity. ③ after completion in vitro steps, through further research in vivo to observe whether it improves the function of MG disease status.